Managing the pools of cellular redox buffers and the control of oxidative stress during the ontogeny of drought-exposed mungbean (Vigna radiata L.)—role of sulfur nutrition - Anjum, Naser A.; Umar, Shahid; Aref, Ibrahim M.; Iqbal, Muhammad (Frontiers in Environmental Science, 2015)
Impacts of increasing environmental stresses (such as drought) on crop productivity can be sustainably minimized by optimizing mineral nutrients (such as sulfur, S). This study, based on a pot-culture experiment conducted in greenhouse condition, investigates S-mediated influence of drought stress (imposed at pre-flowering, flowering and pod-filling stages) on growth, photosynthesis and tolerance of mungbean (Vigna radiata L.) plants. Drought stress alone hampered photosynthesis functions, enhanced oxidative stress [measured in terms of H2O2; lipid peroxidation (LPO); electrolyte leakage (EL)] and decreased the pools of cellular redox buffers (namely ascorbate (AsA); glutathione (GSH)], and the overall plant growth (measured as leaf area and plant dry mass), maximally at flowering stage, followed by pre-flowering and pod-filling stages. Contrarily, S-supplementation to drought-affected plants (particularly at flowering stage) improved the growth- and photosynthesis-related parameters considerably. This may be ascribed to S-induced enhancements in the pools of reduced AsA and GSH, which jointly manage the balance between the production and scavenging of H2O2 and stabilize cell membrane by decreasing LPO and EL. It is inferred that alleviation of drought-caused oxidative stress depends largely on the status of AsA and GSH via S-application to drought-stressed V. radiata at an appropriate stage of plant growth, when this nutrient is maximally or efficiently utilized.